On the Skolem problem and prime powers - Ouaknine, J; Kenison, G; Worrell, J; Lipton, R (Association for Computing Machinery, 2020)
The Skolem Problem asks, given a linear recurrence sequence (un), whether there exists n ∈ N such that un = 0. In this paper we consider the following specialisation of the problem: given in addition c ∈ N, determine whether there exists n ∈ N of the form n = lpk, with k, l ≤ c and p any prime number, such that un = 0.